Systemic Lupus Erythematosus and Vitamin D Deficiency Are Associated with Shorter Telomere Length among African Americans: A Case-Control Study - Hoffecker, Brett M.; Raffield, Laura M.; Kamen, Diane L.; Nowling, Tamara K. (PloS one, 2013)
Systemic lupus erythematosus (SLE) is a chronic systemic autoimmune disease that disproportionately affects African American females. The causes of SLE are unknown but postulated to be a combination of genetic predisposition and environmental triggers. Vitamin D deficiency is one of the possible environmental triggers. In this study we evaluated relationships between vitamin D status, cellular aging (telomere length) and anti-telomere antibodies among African American Gullah women with SLE. The study population included African American female SLE patients and unaffected controls from the Sea Island region of South Carolina. Serum 25-hydroxyvitamin D levels were measured using a nonchromatographic radioimmunoassay. Telomere length was measured in genomic DNA of peripheral blood mononuclear cells (PBMCs) by monochrome multiplex quantitative PCR. Anti-telomere antibody levels were measured by enzyme-linked immunosorbent assay (ELISA). Patients with SLE had significantly shorter telomeres and higher anti-telomere antibody titers compared to age- and gender-matched unaffected controls. There was a positive correlation between anti-telomere antibody levels and disease activity among patients and a significant correlation of shorter telomeres with lower 25-hydroxyvitamin D levels in both patients and controls. In follow-up examination of a subset of the patients, the patients who remained vitamin D deficient tended to have shorter telomeres than those patients whose 25-hydroxyvitamin D levels were repleted. Increasing 25-hydroxyvitamin D levels in African American patients with SLE may be beneficial in maintaining telomere length and preventing cellular aging. Moreover, anti-telomere antibody levels may be a promising biomarker of SLE status and disease activity.